Shaping the Verisimilitude: Moral Didacticism and Neoclassical Principles Responsible for the Rise of the English Novel? - Golban, Petru (Border Crossing, 2016)
The rise of the novel is a major aspect of the eighteenth century British literature having a remarkable typology: picaresque, adventure, epistolary, sentimental, of manners, moral, comic, anti-novel. The comic (including satirical) attitude, social concern, moral didacticism, and other thematically textualized aspects – emerging from both picaresque tradition and neoclassical principles – and together with picaresque tradition and neoclassical principles – are responsible for the emergence of verisimilitude as the forming element responsible in turn for the rise of the literary system of the novel.